2007
DOI: 10.1002/jccs.200700178
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Photocatalytic Efficiency of TiO2 by Supporting on Clinoptilolite in the Decolorization of Azo Dye Direct Yellow 12 Aqueous Solutions

Abstract: Structure and physico-chemical properties of a photocatalyst, especially surface area and absorption ability, were correlated to catalytic activities in photodegradation of dye pollutants in water. In this investigation photocatalytic degradation of azo dye Direct yellow 12 (Chrysophenine G) in water was studied. Titanium(IV) oxide was supported on Clinoptilolite (CP) (Iranian Natural Zeolite) using solid-state dispersion (SSD) method. The results show that the TiO 2 /Clinoptilolite (SSD) is an active photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Apart from the characteristics of semiconductor catalysts and supports, the synthesis method also has a significant influence on the composition and photocatalytic activity of the obtained composite photocatalysts. Up until now, multiple synthetic routes have been carried out to prepare semiconductor-based photocatalysts supported by CP such as hydrothermal [100], photochemical reduction [101], TiCl 4 hydrolysis [102], sol-gel [103], ion exchange [104], physical mixing [105], and SSD [106]. Herein, different methods to prepare TiO 2 /CP composites and their photocatalytic efficiencies in decomposing pollutants are summarized in Table 2, and typical synthetic methods are introduced as follows in detail.…”
Section: Preparation Methods Of Zeolite-based Composite Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the characteristics of semiconductor catalysts and supports, the synthesis method also has a significant influence on the composition and photocatalytic activity of the obtained composite photocatalysts. Up until now, multiple synthetic routes have been carried out to prepare semiconductor-based photocatalysts supported by CP such as hydrothermal [100], photochemical reduction [101], TiCl 4 hydrolysis [102], sol-gel [103], ion exchange [104], physical mixing [105], and SSD [106]. Herein, different methods to prepare TiO 2 /CP composites and their photocatalytic efficiencies in decomposing pollutants are summarized in Table 2, and typical synthetic methods are introduced as follows in detail.…”
Section: Preparation Methods Of Zeolite-based Composite Photocatalystsmentioning
confidence: 99%
“…The massive emission of wastewater containing TC antibiotics caused a serious threat to the environment, ecosystem, and public health owing to their degradation resistance, long half-life, and poor metabolism [129,130]. An Ag/g-C3N4/CP composite with high photoactivity was prepared by ultrasound energy and was used to remove the TC under simulated solar light irradiation [106]. DRS analysis demonstrated that the deposition of Ag NPs could improve the absorption intensity in the simulated solar light region owing to the surface plasmon resonance, and decrease the bandgap resulting in more solar spectrum utilization.…”
Section: Degradation Of Antibioticsmentioning
confidence: 99%
“…The mixture was then dried at 120°C for 5 h in a drying oven and calcined in a furnace at 500°C for 5 h. Then, the obtained TiO2-pillared zeolite was characterized using SEM, XRD, and FTIR spectroscopy. According to Nikazar et al (2007), the proposed incorporation of TiO2 into the zeolite is as shown in Figure 1. (Nikazar et al, 2007)…”
Section: Synthesis Of Tio2-pillared Zeolitementioning
confidence: 99%
“…According to Nikazar et al (2007), the proposed incorporation of TiO2 into the zeolite is as shown in Figure 1. (Nikazar et al, 2007)…”
Section: Synthesis Of Tio2-pillared Zeolitementioning
confidence: 99%